DESIGN OF THE TRAINING – APPROACH FOR IDENTIFICATION OF THE REQUIREMENTS TO THE EDUCATIONAL PROCESS IN THE MILITARY EDUCATION SYSTEM (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
This article considers the design phase of the systems approach to training as a logical link between the results of the learning analysis and the development phase. In this sense, the object of research is the systems approach to training, and its subject is the design of training, in the context of the military education system. The purpose of the article is to provide: (1) an understanding of the content and approach for implementing the training design phase as an element of the systems approach to training; (2) analyzing different approaches for implementing the training design phase; and (3) observations on the features of the training design phase. In the conclusion of the article, the authors substantiate their view that training design, as a stage of the implementation of the systems approach, requires the identification of resources, goals, sequence and environment of training to meet the requirements of the military education system.